2012
DOI: 10.1126/science.1226344
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing Identifies a Basis for Everolimus Sensitivity

Abstract: Tumor genome sequencing reveals the molecular basis of a patient’s unexpected and dramatic response to a cancer drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
420
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(439 citation statements)
references
References 18 publications
7
420
0
2
Order By: Relevance
“…[65][66][67][68] A recent study demonstrated the utility of cancer genomic profiling by linking such mutations in TSC2 to improved survival for UC patients under everolimus treatment. 69 Amplification of RAF1, which has been linked to high-grade tumor, advanced-stage tumor and poor survival in UC, [70][71][72] was also observed in the series, and can be targeted by kinase inhibitors such as Sorafenib, a multikinase inhibitor whose targets include the Raf1 protein (CRAF). Sorafenib has been approved for use in renal cell carcinoma and hepatocellular carcinoma and is under investigation in clinical trials in multiple solid tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68] A recent study demonstrated the utility of cancer genomic profiling by linking such mutations in TSC2 to improved survival for UC patients under everolimus treatment. 69 Amplification of RAF1, which has been linked to high-grade tumor, advanced-stage tumor and poor survival in UC, [70][71][72] was also observed in the series, and can be targeted by kinase inhibitors such as Sorafenib, a multikinase inhibitor whose targets include the Raf1 protein (CRAF). Sorafenib has been approved for use in renal cell carcinoma and hepatocellular carcinoma and is under investigation in clinical trials in multiple solid tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, mutations in TSC1/2 as putative biomarkers that predict efficacy of mTORC1 inhibitors have emerged recently from whole-genome or -exome sequencing analyses of tumor samples from patients who had experienced extraordinary benefit from mTORC1 inhibitor treatments. Solit and colleagues showed that TSC1 loss-of-function mutations were present in one metastatic bladder cancer patient with a durable (>2 years) complete response and four with partial response or stable disease after receiving everolimus, but in only 1 of 9 patients with disease progression (36). Similarly, Voss and colleagues found inactivating mutations in TSC1 or TSC2, or activating mutations in MTOR, in 4 of 6 renal cell carcinoma patients who had durable response to either everolimus or temsirolimus, but not in patients who progressed rapidly on the same treatments (37).…”
Section: Discussionmentioning
confidence: 99%
“…This drug failed a phase II trial for metastatic bladder cancer -but one patient's cancer went away and stayed away for more than two years. Researchers at the Memorial Sloan-Kettering Cancer Center in New York subsequently found that about 8% of people with bladder cancer carry a mutation that makes their tumour susceptible to the drug 6 . The US National Cancer Institute is now examining other reports of rare but significant drug responses through its Exceptional Responders programme, which might see some failed drugs put back into development.…”
Section: Disease Redefinedmentioning
confidence: 99%